Electroactive sugars, organic acids and sugar alcohol analysis in wine using anion-exchange chromatography with electrochemical detection - de Souza, João Carlos [UNESP]; da Silva, José Luiz [UNESP]; Fabrão, Rodrigo Monteiro [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2019)
The present work describes an easy, rapid and sensitive alternative methodology for simultaneous detection of sugars (glucose, fructose and arabinose), organic acids (gluconic, glucuronic and glucaric acids) and sugar alcohol (arabitol) in wine samples. The method is based on high performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD) at gold electrode under detection potential of 0.26 V vs Pd|PdO. The optimized chromatographic anion-exchange separation indicates good separation and detection using a binary gradient with 0.28 mol L −1 CH 3 COONa containing 0.10 mol L −1 NaOH and ultrapure water as mobile phase with a flow rate at 1.0 mL min −1 . Analytical curves presented linear relationship from 1.0 × 10 −7 and 1.0 × 10 −3 mol L −1 with detection limits (S/N = 3) from 3.0 × 10 −8 (glucose) to 9.0 × 10 −7 mol L −1 (gluconic acid). The present method was successfully applied in the determination of sugars, organic acids and sugar alcohols in wine, without time consuming pre-treatment of the sample, no need for organic solvent, fast relative execution time, satisfactory separation, high sensitivity and accuracy.
Keywords: Electrochemical detection; High performance anion-exchange chromatography; Organic acids; Sugar alcohol; Sugars; Wine